A Composite Vascular Risk Index Integrating Flow-Mediated Dilatation, Carotid Intima–Media Thickness and Ankle–Brachial Index for Cardiovascular Stratification in Stable COPD - Dr Shagun; Dr Sunil Sharma; Dr Malay Sarkar; Dr RS Negi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Single vascular biomarkers incompletely capture the excess cardiovascular risk observed in chronic obstructive pulmonary disease (COPD). Objective: To derive and validate an Integrated Vascular Score (IVS; range 0–3) assigning one point each for (i) brachial %ΔFMD < 4 %, (ii) CIMT > 0.8 mm or plaque ≥ 1.2 mm, and (iii) ABI < 0.90 or > 1.40, and to compare its predictive utility with that of the individual components. Methods: The IVS was calculated for 84 Himalayan adults (43 stable COPD, 41 controls) in whom all three vascular tests were available. Clinical end-points were GOLD group C/D, CAT ≥ 21, and ≥ 2 exacerbations in the preceding year. Discrimination was assessed with receiver-operating-characteristic (ROC) curves and compared by DeLong tests. Results: Score distribution differed strikingly between groups (controls: IVS 0 83 %, 1 15 %, ≥ 2 2 %; COPD: IVS 0 5 %, 1 16 %, 2 47 %, 3 32 %). IVS correlated strongly with GOLD stage (Spearman ρ 0.62, p < 0.001). A threshold ≥ 2 predicted GOLD C/D with 88 % sensitivity and 92 % specificity (AUC 0.93, 95 % CI 0.86–0.99), exceeding the best single biomarker (CIMT AUC 0.81, p = 0.04). AUCs for CAT ≥ 21 and frequent-exacerbator phenotype were 0.89 and 0.78 respectively. Calibration was satisfactory (Hosmer–Lemeshow p = 0.64) and a bedside nomogram showed good agreement with observed risk. Conclusions: A simple additive IVS out-performs isolated FMD, CIMT or ABI for identifying high-risk COPD phenotypes. An IVS ≥ 2 may trigger intensified statin or antiplatelet therapy pending multicentre validation.